2015
DOI: 10.1016/bs.mie.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Seq

Abstract: RNA molecules contain a variety of chemically diverse, posttranscriptionally modified bases. The most abundant modified base found in cellular RNAs, pseudouridine (Ψ), has recently been mapped to hundreds of sites in mRNAs, many of which are dynamically regulated. Though the pseudouridine landscape has been determined in only a few cell types and growth conditions, the enzymes responsible for mRNA pseudouridylation are universally conserved, suggesting many novel pseudouridylated sites remain to be discovered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The RT signatures in question may comprise nucleotide misincorporation or transcription arrest, and frequently originate from nucleotide modification at the position of interest. Several library preparation protocols have been published that capture cDNA from abortive RT [16,20,22,23] and can therefore be fully exploited by CAn. However, even preparation methods that do not capture abortive cDNA may provide useful information by providing misincorporation signals that may be analyzed by CAn.…”
Section: Resultsmentioning
confidence: 99%
“…The RT signatures in question may comprise nucleotide misincorporation or transcription arrest, and frequently originate from nucleotide modification at the position of interest. Several library preparation protocols have been published that capture cDNA from abortive RT [16,20,22,23] and can therefore be fully exploited by CAn. However, even preparation methods that do not capture abortive cDNA may provide useful information by providing misincorporation signals that may be analyzed by CAn.…”
Section: Resultsmentioning
confidence: 99%
“…Although numerous studies have revealed that pseudouridines in small cellular RNAs are important for maintaining their structures [5,7,11], the functional roles of pseudouridylation in mRNA translation and its contextual sequence features still remain largely unclear. Several high-throughput experimental techniques of characterizing pseudouridines across transcriptome have been developed recently [19][20][21][22], detailed transcriptome-wide landscape, functions and molecular mechanisms of pseudouridines in post-transcriptional regulation are still to be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The pseudouridine modification site data were downloaded from the RMBase database [57] which includes the high-throughput profiling data of pseudouridines collected from three recent experimental strudies [19,20,22]. All the labelled pseudouridine sites were separated into a human dataset and a mouse dataset.…”
Section: Data Collection and Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…Current techniques such as pseudo-seq, piloted by Wendy Gilbert and coworkers, 92 will allow for transcriptome-wide mapping of these sites in human cells. These modifications can affect ribosome function, as it has been shown that one pseudouridylation modification present in a stop codon allows for translational read-through by the ribosome 93 .…”
Section: Introductionmentioning
confidence: 99%